Physico-chemical changes, microbiological properties and storage shelf life of cow and goat milk from industrial high-pressure processing - tan, Sok Fern; Nyuk, Ling Chin; Tee, Tuan Poy; Chooi, Sook Kuan (MDPI, 2020)
Industrial high-pressure processing (HPP) was conducted on cow and goat milk in comparison to conventional heat pasteurization. No significant changes were found in the physico-chemical properties of the treated milk except for pH, where pasteurized cow milk experienced a decrease while goat milk’s pH increased for both pasteurized and HPP treated. HPP-treated cow and goat milk both achieved microbial shelf life of 22 days at 8 °C storage with no increase in Bacillus cereus, mesophilic aerobic spores, coliform, yeast and mold but slight increase in psychrotrophic bacteria and total plate count. Pasteurized goat milk was spoilt at the end of storage with exceeding count of psychrotrophic bacteria (9.0 × 108 CFU/mL) and total plate count (3.5 × 108 CFU/mL). HPP-treated cow milk exhibited higher physico-chemical stability than goat milk as evidenced by non-significant change of titratable acidity but goat milk experienced an increase of 0.04% averagely.